Publications Received (Academy of Management Review, 1988)
The article presents a list of publications received by the journal including “A Woman's Place: Management,” by Connie Sitterly and Beth Duke, “Working it Out: Sanity & Stress in the Workplace,” by Stephen Strasser, and “Unlocking: A Guide to Creative Living,” by Daniel Sandowsky.